Comportamento infantil contemporâneo: características da geração Alpha da perspectiva dos pais - Rangel, Maysa Fagundes Pereira (2020)
The globalized, technological, postmodern world, full of historical, social and cultural transformations, has given rise to the emergence of new forms of social organization, lifestyles and relationships. Children, integrated in this context, manifest similar repercussions in the expression of their uniqueness and the students of generational theory consider them as representatives of a new generation, called Alpha. In order to investigate the main characteristics and behaviors of children in contemporary times attributed by parents, the implications of these characteristics in their relationships with family and peers, the factors that influenced changes in child behavior and the parents' perception of educating children today , the present research of the exploratory-descriptive type, of quantitative and qualitative method, had the social constructionism as an epistemological approach and the systemic view of the phenomena as a theoretical reference. 114 parents of children born from 2010 participated in the study as respondents to the questionnaire and couples from 8 families with children up to 10 years old were interviewed. The results contributed to identify the children's behaviors and characteristics, from the parents 'perspective, and to understand the differences that were associated with the generations that emerged from the comparison of the parents' and children's childhood, as well as, to verify the implications that the social context and relational exercise in this perception of differentiation and about educating children today